ЯРИМЎТКАЗГИЧЛИ ҚУЁШ ЭЛЕМЕНТЛАРИ ВА УЛАРДАН ФОЙДАЛАНИШ ИМКОНИЯТЛАРИНИ ФИЗИКА ТАЪЛИМИГА ЖОРИЙ ЭТИШ - Сатторов, А.А. (SCIENCE and SOCIETY, 2021)
The article studies the possibilities of forming the physical foundations of non-traditional energy sources in the educational program of general schools and lyceums. And also, a number of methodological recommendations are given regarding the teaching of the physical and technological foundations of the conversion of solar energy into electrical energy.
Keywords: unconventional energy source; solar energy; teaching physics; photoelectric effect; solar power plants; inverter